Correlation of structural, transport and magnetic properties in La1−xZrxMnO3 manganite samples. Issue 10 (1st August 2016) - Shelke, A.R.; Ghodake, G.S.; Kim, D.-Y.; Ghule, A.V.; Kaushik, S.D.; Lokhande, C.D.; Deshpande, N.G.
Abstract: In the present work, La1− x Zr x MnO3 (where x =0.05, 0.10, 0.15 and 0.20) powder samples are synthesized using solid-state reaction and investigated for structural, electrical and magnetic properties using X-ray diffraction, neutron diffraction, FT-IR, resistivity measurement system and SQUID. Structural investigations revealed that all the samples have rhombohedral structure with R 3 ¯ C space group. Moreover, it was observed that the MnO6 octahedra gets rotated due to internal stress after replacement of 'La' with 'Zr' and results into the bending of Mn–O–Mn bond angle from standard 180°. This is supported by FTIR wherein, the stretching bond vibrations produce distortion in the Mn-O-Mn symmetry. Evolution in the granular morphology from the irregular shape to the interconnected hexagon shape is found with increase in 'Zr' concentration. XPS studies revealed 'Mn' having mixed valence state of Mn 3+ and Mn 4+, indicating hole-doping behavior. Decrease in resistivity and increase in metal-insulator transition temperature is observed with increase in 'Zr' concentration upto 15%. Furthermore, the magnetic saturation is found to increase upto 15% Zr concentration, beyond which it decreases, significantly. A strong correlation between the phase formations, structural, magnetic and transport properties as a function of 'Zr' concentration is revealed.